THE INFLUENCE OF GLOBAL MARKETING TRENDS ON THE UPDATE OF MEDICAL MARKETING TOOLS - BUDNIKEVYCH, IRYNA; KOLOMYTSEVA, OLENA; SHPAYUK, OLEKSANDR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the impact of global marketing trends on the updating of medical marketing tools that are becoming more customer-oriented, patient-centered, personalized, service, digitalized, partner and socially oriented. The impact of the COVID-19 pandemic on the activities of health care providers, investors and consumers is considered. It is noted that new marketing technologies and tools, innovation of medical processes, active digitalization, global automation of customer service and medical services, changing priorities from "disease medicine" to "health medicine" distinguish modern marketing in the medical field. It is emphasized that today the world’s venture investments are actively directed to digital medicine - Digital Health. Among the global marketing trends are: telemedicine, voice search, chatbots and messengers; content marketing and interactive content; data-based marketing and management; mobile marketing and mobile devices; "Uberization of consumption", innovative marketing campaigns, portals and aggregators; working with feedback and reputation management; testing and screening; outsourcing, consolidation, mergers and acquisitions; development of new market niches, "retailization" of medicine and others. The digitalization of medical marketing has strongly covered both the medical market in general and the laboratory segment in particular, offering a large number of tools, services, platforms, projects, moving towards the creation of multifunctional platforms and marketplaces. It is concluded that the market of medical services is transformed under the influence of global, national and regional factors, its participants reorient the provision of medical and social services to create values, increase efficiency, optimize production and marketing costs, improve logistics, develop medical and laboratory retail, methods, tools and technologies of marketing, improve the service component, are actively involved in the digitalization of marketing tools and digitization of medical and laboratory processes. It is noted that it is necessary to develop special tools for rapid audit of medical institutions on the main queries in Google, ranking market players on the criteria of accuracy, comfort, safety, expertise, establishing stable online communications with patients, choosing the most relevant health insurance program, etc.